Sequence Changes Modulate Peptoid Self-Association in Water - Fuller, Amelia A.; Jimenez, Christian J.; Martinetto, Ella K.; Moreno, Jose L.; Calkins, Anna L.; Dowell, Kalli M.; Huber, Jonathan; McComas, Kyra N.; Ortega, Alberto (Frontiers in Chemistry, 2020)
Peptoids, N-substituted glycine oligomers, are a class of diverse and sequence-specific peptidomimetics with wide-ranging applications. Advancing the functional repertoire of peptoids to emulate native peptide and protein functions requires engineering peptoids that adopt regular secondary and tertiary structures. An understanding of how changes to peptoid sequence change structural features, particularly in water-soluble systems, is underdeveloped. To address this knowledge gap, five 15-residue water-soluble peptoids that include naphthalene-functionalized side chains were designed, prepared, and subjected to a structural study using a palette of techniques. Peptoid sequence designs were based on a putative amphiphilic helix peptoid bearing structure-promoting (S)-N-(1-naphthylethyl)glycine residues whose self-association in water has been studied previously. New peptoid variants reported here include sequence changes that influenced peptoid conformational flexibility, functional group patterning (amphiphilicity), and hydrophobicity. Peptoid structures were evaluated and compared using circular dichroism spectroscopy, fluorescence spectroscopy, and size exclusion chromatography. Spectral data confirmed that sequence changes alter peptoids' degree of assembly and the organization of self-assembled structures in aqueous solutions. Insights gained in these studies will inform the design of new water-soluble peptoids with regular structural features, including desirable higher-order (tertiary and quaternary) structural features.